The other government: state-owned enterprises in Germany and their implications for the core public sector - Asatryan, Zareh; Heinemann, Friedrich; Nover, Justus (ZEW-Kurzexpertise, 2022)
This paper aims to raise the awareness and knowledge about state-owned enterprises (SOEs) in Germany - a sizable but often ignored part of the overall public sector which the authors of this ZEW expert brief, therefore, label the "other government" - to facilitate an informed debate about the full scale of fiscal activities and economic involvements of governments. Whereas SOEs are influenced by public decision makers in their agenda setting and are in principle part of the public sector, their role and activities are much less frequently discussed in public and scientific debates or official statistics which typically concentrate on governments' core budgets.
Keywords: 2008-2019; Graue Literatur